Monitoring the elimination of gambiense human African trypanosomiasis in the historical focus of Batié, South-West Burkina Faso - Compaoré, C.; Kaboré, J.; Ilboudo, H.; Thomas, Lian F.; Falzon, Laura C.; Bamba, M.; Sakande, H.; Koné, M.; Kaba, D.; Bougouma, C.; Adama, I.; Amathe, O.; et al. (EDP Sciences, 2022)
The World Health Organisation has targeted the elimination of human African trypanosomiasis (HAT) as zero transmission by 2030. Continued surveillance needs to be in place for early detection of re-emergent cases. In this context, the performance of diagnostic tests and testing algorithms for detection of the re-emergence of Trypanosoma brucei gambiense HAT remains to be assessed. We carried out a door-to-door active medical survey for HAT in the historical focus of Batié, South-West Burkina Faso. Screening was done using three rapid diagnostic tests (RDTs). Two laboratory tests (ELISA/T. b. gambiense and immune trypanolysis) and parasitological examination were performed on RDT positives only. In total, 5883 participants were screened, among which 842 (14%) tested positive in at least one RDT. Blood from 519 RDT positives was examined microscopically but no trypanosomes were observed. The HAT Sero-K-Set test showed the lowest specificity of 89%, while the specificities of SD Bioline HAT and rHAT Sero-Strip were 92% and 99%, respectively. The specificity of ELISA/T. b. gambiense and trypanolysis was 99% (98-99%) and 100% (99-100%), respectively. Our results suggest that T. b. gambiense is no longer circulating in the study area and that zero transmission has probably been attained. While a least cost analysis is still required, our study showed that RDT preselection followed by trypanolysis may be a useful strategy for post-elimination surveillance in Burkina Faso.